Pseudophaeocytostroma bambusicola gen. et sp. nov. (Diaporthaceae) from bamboo in Yunnan, P.R. China - Monkai, Jutamart; Phookamsak, Rungtiwa; Xu, Sheng; Xu, Jianchu; Mortimer, Peter E.; Karunarathna, Samantha C.; Suwannarach, Nakarin; Lumyong, Saisamorn (Phytotaxa, 2022)
Phaeocytostroma species (Diaporthaceae, Diaporthales, Sordariomycetes) are mainly associated with grasses (Poaceae) and are considered important pathogens of maize and sugarcane. In the present study, a phaeocytostroma-like taxon was collected from bamboo culms in Yunnan, China and characterized using morphological and multigene phylogenetic analyses. The fungus was characterized by uni- to bi-locular conidiomata, papillate ostioles, septate, filiform paraphyses and brown, oblong to ellipsoid, aseptate, conidia, with obtuse ends. Phylogenetic analyses inferred from the combined dataset of ITS, LSU, and TEF1-α regions showed that the phaeocytostroma-like taxon constituted an independent lineage clustered with P. sacchari distant from Phaeocytostroma sensu stricto. Hence, the novel genus Pseudophaeocytostroma is introduced to accommodate the new species Ps. bambusicola. Pseudophaeocytostroma bambusicola clustered with P. sacchari strains CBS 275.34, km-1, UMICH-1, 135 in the present phylogenetic analyses. However, these strains are not the ex-type strains of P. sacchari and some of them lack morphological descriptions and remain unpublished. Therefore, we treat these strains as Ps. “sacchari” herein until the type strain of P. sacchari is verified. The pairwise nucleotide comparison of ITS and TEF1-α sequence data and a pairwise homoplasy index test between Ps. bambusicola and Ps. “sacchari” provided further evidence to support Ps. bambusicola as a distinct species. The morphological characteristics and phylogenetic relationship of Ps. bambusicola and other related Phaeocytostroma species are also compared and discussed.